Efficacy of Bimodal High-Voltage Monopulsed Current in the Treatment of Pressure Ulcer: A Systematic Review - Zhiwei ZHANG; Bojun LI; Zhichao WANG; Lina WU; Lili SONG; Yexiang YAO (Tehran University of Medical Sciences, 2019)
Background: We aimed to systematically evaluate the efficacy of high-voltage pulsed current (HVPC) in the treatment of pressure ulcer. Methods: We searched the databases of PubMed, Cochrane Library, Elsevier and EMBASE to identify randomized controlled studies on the application of HVPC in pressure ulcer treatment, up to January 2019. Two authors independently screened the literature according to the inclusion and exclusion criteria, extracted the data and evaluated the quality. RevMan 5.3 software was used for statistical analysis. Four randomized controlled trials involving a total of 176 patients were included in the study. Results: Meta-analysis showed that the percentage of wound area reduction in the HVPC treatment group was higher than that in the control group (95%CI 24.59, 47.76, P<0.001). Descriptive analysis showed that there was no significant difference in wound healing between the HVPC treatment group and the control group. One study reported that there was contact dermatitis, and the rest of the studies reported no adverse events. Conclusion: Compared with the conventional therapy, the combination with HVPC therapy can reduce the area of pressure ulcers more effectively. However, due to the small number of the studies included in this evaluation, the conclusions need to be verified by more high-quality studies.